Borders, mobility and the transborder space: Reflections for a discussion - Marcela Aurora Tapia Ladino (Estudios Fronterizos, 2017)
The purpose of this manuscript is to contribute to the discussion of transborder and border issues based on border studies in order to develop an explanatory framework that allows one to understand what makes a border region or space a transborder region or space. The consideration of scale and perspective from the territory under analysis is important for understanding this shift. We theorize that a region or space becomes transborder mainly through the interaction produced by the constant crossing and mobility of people as well as the deployment of a series of social practices in which the border is both a reference and a resource.